The Practicality of Student Worksheets (LKPD) Based on Predict Observe Explain (POE) in Mathematics Learning - Suriani, Teni; Yolanda, Nela Sari; Perdana, Dina Novarina; Utami, Khurnia Budi (The Future of Education Journal, 2025)
Teaching materials in schools, such as textbooks and regular Student Worksheets (LKPD), typically only contain summaries of the material and questions, and still lack steps for a learning model. This results in students being less active in the learning process. This study aims to assess the practicality of Student Worksheets (LKPD) based on the Predict Observe Explain (POE) model in mathematics learning. The Predict Observe Explain learning model helps students understand and discover concepts by providing steps that encourage students to express their ideas. The development model used in this study is Research & Development (R&D). The stages of this model include: 1) potential and problems, 2) information gathering, 3) product design, 4) product validation, 5) product revision, and 6) product testing. The population in this study consisted of 20 students from Grade XI at Ekasakti High School, Padang, for the academic year 2024/2025. The results of the study indicate that the practicality of the LKPD was rated as very practical, based on the practicality assessment from both teachers and students. Therefore, it can be concluded that the Student Worksheet (LKPD) based on the Predict Observe Explain (POE) model is feasible and practical for students to use in mathematics learning, specifically in the topic of matrices.